Development and implementation of an advanced shipborne integrated platform for water quality inspection - Li, Chao; Song, Yu-Ze; Si, Hui-Min (Frontiers in Marine Science, 2024)
Monitoring the quality of marine water is crucial for ensuring the health and sustainability of marine ecosystems. The conventional monitoring approach involves manual sampling using a water sampler, followed by packaging the water samples in plastic bottles and transporting them to a terrestrial laboratory for analysis. However, this method is time consuming, labor intensive, and cannot provide real-time data for addressing unforeseen circumstances. In response to these challenges, an advanced shipborne integrated platform for water quality inspection (ASIPWQI) has been proposed and implemented. This system automates the collection of multi-layer seawater samples in the vertical profile, conducts online measurements of monitoring elements, and provides real-time measurement data. In multiple sea trials, ASIPWQI successfully conducted on-site collection and measurement of a significant number of samples, meeting the water quality monitoring requirements in China’s nearshore waters. Comparative analysis of the laboratory measurement results for nutrients, heavy metals, and total phosphorus and nitrogen in water samples collected using automatic and manual methods revealed no significant differences between the two sampling approaches and demonstrated strong correlation. Further analysis using practical relative error (PRE) statistical methods showed that the data rate of most monitoring elements with relative errors less than 10% was higher than 70%, with nitrite, silicate, and phosphate even exceeding 90%. This indicate that ASIPWQI has excellent stability and applicability, offering a viable alternative to traditional manual sampling and laboratory testing. This innovation makes water quality monitoring significantly more efficient.